ANALISIS UPAYA SEKOLAH DALAM MENGATASI KONFLIK ANTAR SISWA DI SMAN 1 KERITANG KECAMATAN KERITANG KABUPATEN INDRAGIRI HILIR - Sesri Resdiani; Achmad Hidir (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
This research was conducted in Kotabaru Village Keritang Sub-district Indragiri Hilir Regency with the aim to obtain information about school efforts in resolving conflict in SMAN 1 Keritang. Some of the problems in this research are (1) How is the effort of school to overcome conflict between student in SMAN 1 Keritang Keritang Sub-district Indragiri Hilir Regency? (2) What are the constraints faced by schools in the effort to solve conflicts between students in SMA Negeri 1 Keritang Keritang Sub-district Indragiri Hilir regency? the title of this research is "Analysis of School Efforts in Overcoming Inter-Student Conflicts at SMAN 1 Keritang Keritang Sub-district Indragiri Hilir Regency." The research aimed to find out how the school efforts in resolving conflict among students in SMAN 1 Keritang Keritang Sub-district Indragiri Hilir Regency. To find out what constraints faced by schools in an effort to resolve conflicts between students in SMAN 1 Keritang Keritang District Indragiri Hilir Regency. This research is a qualitative research because it is case-shaped, the subject of this research is the teacher at SMAN 1 Keritang and the students directly involved in the conflict in the form of brawl and fight in SMAN 1 Keritang as many as 8 subjects. In doing data collection using observation, interview, and documentation. To analyze the problems in this study using qualitative analysis and will be described descriptively in writing. After doing this research, the result of this research is known that school effort in resolving conflict between students at SMAN 1 Keritang is by making various policies such as: making of school order, extracurricular activity, giving sanction which is assertive but educational. With the policy, the intensity of fighting decreased though not optimal.Keywords : school efforts, resolve, student conflict